Exploration of Connection between Culture, Corporate Communication and Consumption with the Help of Focus Groups:An Empirical Study - Datta, Debraj; Datta, Mahua (Indian Journal of Marketing, 2009)
The field of consumer behaviour studies deals with how individuals, groups and organisations select, buy, use and dispose off products and experiences to satisfy their needs and desires. In the process, consumers process brands and marketing promotions for meaning as well as for information. Interpretation of brands and marketing promotions is a problematic issue for both consumers and marketers. First, consumers construct different meanings than what brand sponsors may have intended. Furthermore, different types of consumers construct multiple meanings, depending on personal background, contexts of consumption and multiple frames of reference. This issue of brands, ads, and promotions possessing several potential meanings has significant implications for marketing theory and practice. The present study aims at understanding the purchase decision-making pattern among various communities in India and the effect of various cultural profiles in terms of language or religion or both. For the survey, the respondents were chosen from three linguistic groups viz. Bengalis, Marwaris and Gujarati and three religious groups viz. Hindus, Muslims and Jains and focus group technique was used. Focus groups are discussions in which the moderator supplies the topics and monitors the discussion. The purpose is to gather information about a specific or focused topic in a group environment, allowing for discussion and interaction by the participants.